The development of the NUCLEUS FREEDOM cochlear implant system. - Patrick JF; Busby PA; Gibson PJ (Trends in Amplification, 2006)
Cochlear Limited (Cochlear) released the fourth-generation cochlear implant system, Nucleus Freedom, in 2005. Freedom is based on 25 years of experience in cochlear implant research and development and incorporates advances in medicine, implantable materials, electronic technology, and sound coding. This article presents the development of Cochlear's implant systems, with an overview of the first 3 generations, and details of the Freedom system: the CI24RE receiver-stimulator, the Contour Advance electrode, the modular Freedom processor, the available speech coding strategies, the input processing options of Smart Sound to improve the signal before coding as electrical signals, and the programming software. Preliminary results from multicenter studies with the Freedom system are reported, demonstrating better levels of performance compared with the previous systems. The final section presents the most recent implant reliability data, with the early findings at 18 months showing improved reliability of the Freedom implant compared with the earlier Nucleus 3 System. Also reported are some of the findings of Cochlear's collaborative research programs to improve recipient outcomes. Included are studies showing the benefits from bilateral implants, electroacoustic stimulation using an ipsilateral and/or contralateral hearing aid, advanced speech coding, and streamlined speech processor programming.